2019
DOI: 10.3390/ijms20153678
|View full text |Cite|
|
Sign up to set email alerts
|

Poly(2,6-Dimethyl-1,4-Phenylene Oxide)-Based Hydroxide Exchange Separator Membranes for Zinc–Air Battery

Abstract: Rechargeable zinc–air batteries are deemed as the most feasible alternative to replace lithium–ion batteries in various applications. Among battery components, separators play a crucial role in the commercial realization of rechargeable zinc–air batteries, especially from the viewpoint of preventing zincate (Zn(OH)42−) ion crossover from the zinc anode to the air cathode. In this study, a new hydroxide exchange membrane for zinc–air batteries was synthesized using poly (2,6-dimethyl-1,4-phenylene oxide) (PPO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 24 publications
(49 reference statements)
0
40
0
Order By: Relevance
“…H ads + H ads H 2 (11) To further conceptualize the charge transfer, the CV plots for both the Zn/IF and Zn/NF anodes were obtained at various scan rates (5 to 20) mV/s in the electrolyte (Figure 6a,b). It is observed that when scan rates increased, the anodic peak currents linearly increased.…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation
“…H ads + H ads H 2 (11) To further conceptualize the charge transfer, the CV plots for both the Zn/IF and Zn/NF anodes were obtained at various scan rates (5 to 20) mV/s in the electrolyte (Figure 6a,b). It is observed that when scan rates increased, the anodic peak currents linearly increased.…”
Section: B)mentioning
confidence: 99%
“…Unlike lithium (Li), Zn is more cost-effective (~$0.9/lb) and globally abundant (~300 times higher than Li in the earth's crust) [9,10]. A Zn anode offers greater safety and a higher specific volumetric capacity (5855 mAh/cm 3 ) compared to that of Li (2066 mAh/cm 3 ) [11,12]. Furthermore, Zn is primarily used in industry and can be easily recycled using existing technologies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Abbasi et al [66] prepared poly (p-phenylene oxide) (PPO)-based AEMs using three different cations-trimethylamine (TMA), 1-methylpyrolidine (MPY), and 1-methylimidazole (MIM)-and tested them in a Zn-air battery. PPO-TMA and PPO-MPY exhibited low zincate diffusion coefficients (1.13 × 10 −8 , and 0.28 × 10 −8 cm 2 /min, respectively) and high discharge capacity (about 800 mAh/g Zn using PPO-TMA).…”
Section: Advances In Aems For Alkali Metal-air Batteriesmentioning
confidence: 99%
“…Zinc-air batteries (ZABs) have exhibited high potential for various energy applications because of their cost effectiveness and very high energy density (1.35 kWh/kg) [7][8][9][10]. Zinc (Zn) is an attractive electrode material because it is light-weight, non-toxic, inherently safe, inexpensive, and abundant [11,12].…”
Section: Introductionmentioning
confidence: 99%